THE ANALYSIS OF THE THEORY OF SOCIAL CAPITAL ON THE EXAMPLE OF ASIAN AND EUROPEAN COUNTRIES: COMPARATIVE APPROACH - Arushan Arushanovich Vartumyan; Alexander Valerievich Polyakov (Современная наука и инновации)
In the present article deals with the theory of social capital, including the theory of dictatorship. The authors present the evolution of the Asian socialist countries, the interaction between state institutions, the political community, civil society and the corporate economy. Comparing the model and the political configuration in the countries of Asia (China, South Korea, Thailand) and Italy concluded that civilian cooperation at an unacceptably low level, gives the model of political participation «clientelistic» character, mends obstacles the development of democracy.